MENCARI FORMAT JURNALISME PUBLIK DI ERA DIGITAL : (STUDI KASUS PROJECT MULTATULI) - Nasrullah Kusadjibrata; Ardan Ahmad; Retno Intani; Kevino Velrahga (Jurnal Komunikasi & Media Digital, 2023)
This study aims to determine the editorial management run by Multatuli Project online media and to know the role of online media editorial management of Multatuli Project in realizing public journalism. This research uses a constructivist paradigm with a descriptive case study approach. The methods used are (1) interview, (2) observation, (3) documentation. The research object is Multatuli Project online media with the focus of the research being the editorial management of Multatuli Project. This research found two findings. First, the public journalism built by the Multatuli Project is a commitment to those who are marginalized and to keep their distance from the oligarchs. Second, editorial management, which among other things, at the editorial meeting level provides opportunities for the public who are not part of the editorial team to participate in editorial meetings. Keywords: public journalism; Multatuli project; editorial management